FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH DI KECAMATAN SEMAMPIR SURABAYA[Risk Factors Associated with Low Birth Weight at Semampir District, Surabaya] - Amima Fajriana; Annas Buanasita (Universitas Airlangga, 2018)
Low Birth Weight (LBW) is one of the biggest causes of neonatal mortality in Indonesia. The prevalence of LBW at Semampir District in Surabaya tended to increase from 5.74% in 2013 to 13.65% in 2015. LBW caused by multi-factors including internal factors such as fetal, placental and maternal, and also external factors such as lifestyle and environment. This study aimed to analyze the association between maternal age, gestational age, Mid Upper-Arm Circumference (MUAC), Hemoglobin (Hb) levels, environmental tobacco exposure and LBW at Semampir District, Surabaya. The respondents were mothers at Semampir District who gave birth in 2016. The design of this study was case control. The sample consisted of 22 mothers from the control group and 22 mothers from the case group. The result of descriptive analysis respectively showed that in case group (40.6%) and control group (13.6%) were not pregnant in healthy reproductive age. 59.1% and 18.1% gave birth when the gestational age <37 weeks. 41% and 9.1% were suffered of chronic energy malnutrition (MUAC <23.5). 40.9% and 22.7% were anemic. Moreover, 90,9% and 77,2% were exposed to tobacco smoke (secondhand smoke exposure). Chi square analysis with α=0,05 showed that there were significance associations between gestational age (p=0,006) (OR=6,198; CI 95%=1,61-27,88) and MUAC (p=0,018) (OR=6,623; CI 95%=1,327-51,2) with LBW. It is concluded that mother who gave birth to a premature baby were 6,2 times more likely to have LBW, whereas mother who suffered from chronic energy malnutrition were 6,6 times more likely to have LBW baby.